Aluminum alloy ingot, motor rotor of asynchronous motor, asynchronous motor, power assembly and electric vehicle

The aluminum alloy ingot with controlled silicon, magnesium, nickel, cerium, and iron composition addresses the strength and deformation issues of high-speed AC asynchronous motors by forming strengthening phases, ensuring resistance to thermal cracking and maintaining electrical conductivity.

CN119194184APending Publication Date: 2024-12-27HUAWEI DIGITAL POWER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411203718.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing high-purity aluminum cast rotors used in AC asynchronous motors for new energy vehicles cannot meet the strength and deformation requirements at high speeds due to high nickel and copper content, leading to increased production costs and low yield strength, while also being prone to thermal deformation.

Method used

An aluminum alloy ingot composed of specific ratios of silicon, magnesium, nickel, cerium, and iron, with controlled impurity levels, forms strengthening phases like MgSi and α-Fe phases during casting, enhancing mechanical properties and electrical conductivity.

Benefits of technology

The aluminum alloy ingot provides resistance to thermal cracking, excellent yield strength at room and high temperatures, and improved electrical conductivity, meeting the strength and deformation demands of high-speed asynchronous motors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194184A_ABST
    Figure CN119194184A_ABST
Patent Text Reader

Abstract

The invention provides an aluminum alloy ingot, a motor rotor of an asynchronous motor, the asynchronous motor, a power assembly and an electric vehicle, raw material components of the aluminum alloy ingot are composed of aluminum, silicon, magnesium, nickel, cerium, iron and impurities, in the raw material components, the mass percentages of the silicon, the magnesium, the nickel, the cerium and the iron in the raw material components are within [0.5%, 2.5%], [0.2%, 1.0%], [0, 2.5%], [0.01%, 0.5%] and (0, 0.2%), and the balance is aluminum. The sum of the mass percents of silicon, magnesium, nickel, cerium and iron in the raw material components is less than or equal to 5%, and the content of the impurities is less than or equal to 0.3%. The yield strength, the conductivity, the extensibility and the heat crack resistance are comprehensively considered, various properties are balanced through the combined effect of all the elements, and the aluminum alloy ingot with the excellent comprehensive properties such as the yield strength larger than 100 MPa is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of asynchronous motors, and in particular to an aluminum alloy ingot, a motor rotor of an asynchronous motor, an asynchronous motor, a power assembly and an electric vehicle. Background Art

[0002] The AC asynchronous motors used in new energy vehicles usually use cast aluminum rotors. Currently, high-purity aluminum such as Al99.6 and Al99.7 are mainly used for rotor casting. With the increasing demand for the maximum speed of the vehicle, the peak speed of the motor has also increased from the original 18,000 rpm to 21,000 rpm, and even exceeded 25,000 rpm. The pure aluminum cast aluminum squirrel cage can no longer meet the strength and deformation requirements of the maximum speed and overspeed. It is urgent to improve the strength of cast aluminum and reduce the deformation of cast aluminum at high speed. Aluminum alloy is a material that is conducive to lightweight equipment. By adjusting the different elements of aluminum alloy, aluminum alloy can have different properties such as high thermal conductivity, high electrical conductivity, high yield strength, corrosion resistance, high toughness, and high hardness. However, the nickel content and copper content of the aluminum alloy currently used for cast aluminum rotors are high, the production cost is high, and the yield strength is low. The development of aluminum alloy materials with high strength and good electrical conductivity has become an important demand for the high-speed development of asynchronous motors. Summary of the invention

[0003] The present application provides an aluminum alloy ingot, a motor rotor of an asynchronous motor, an asynchronous motor, a power assembly and an electric vehicle.

[0004] In a first aspect, the present application provides an aluminum alloy ingot, wherein the raw material components of the aluminum alloy ingot are composed of aluminum, silicon, magnesium, nickel, cerium, iron and impurities, wherein:

[0005] The mass percentage of silicon in the raw material components is within [0.5%, 2.5%];

[0006] The mass percentage of magnesium in the raw material components is within [0.2%, 1.0%];

[0007] The mass percentage of nickel in the raw material components is within [0, 2.5%];

[0008] The mass percentage of cerium in the raw material components is within [0.01%, 0.5%];

[0009] The mass percentage of iron in the raw material components is within (0, 0.2%];

[0010] The sum of the mass percentages of silicon, magnesium, nickel, cerium and iron in the raw material components is less than or equal to 5%, and the remaining components are aluminum and impurities, and the impurity content is less than or equal to 0.3%.

[0011] In the embodiments of the present application, in the Al-Si-Mg alloy, magnesium (Mg) and silicon (Si) are the main strengthening elements, which mainly form a series of MgSi strengthening phases, such as Mg2Si, Mg5Si6, etc., after casting or heat treatment, to improve the mechanical properties of the aluminum alloy. Magnesium (Mg) and silicon (Si) can also form nano-scale β"-Mg5Si6 phase and β-Mg2Si phase during high-temperature smelting and casting, which serve as strengthening phases to improve the mechanical properties of the aluminum alloy.

[0012] In the embodiment of the present application, in the Al-Mg-Si alloy, a small amount of Si can effectively promote the nucleation of the strengthening phase MgSi phase, thereby improving the mechanical properties and effectively reducing the thermal cracking tendency of the alloy. However, when the Si content is too high, the alloy can form massive eutectic silicon at the grain boundary, which is not conducive to the mechanical properties and electrical conductivity of the alloy, and also increases the tendency of the alloy to intergranular corrosion.

[0013] Consider the amount of Mg5Si6 phase and Mg2Si phase generated and the strength and electrical conductivity of the aluminum alloy ingot. In one embodiment, the mass percentage of silicon in the raw material component is within [0.5%, 2.3%]. In one embodiment, the mass percentage of silicon in the raw material component is within [0.5%, 2.0%]. In one embodiment, the mass percentage of silicon in the raw material component is within [0.5%, 1.5%]. In one embodiment, the mass percentage of silicon in the raw material component is within [0.5%, 1.0%]. In one embodiment, the mass percentage of silicon in the raw material component is within [0.5, 1.2%]. In one embodiment, the mass percentage of silicon in the raw material component is within [1.5%, 2.5%]. In one embodiment, the mass percentage of silicon in the raw material component is within [2.0%, 2.5%]. In one embodiment, the mass percentage of silicon in the raw material component is 0.5%. In one embodiment, the mass percentage of silicon in the raw material component is 1.0%. In one embodiment, silicon accounts for 1.5% by weight of the raw material components. In one embodiment, silicon accounts for 2.0% by weight of the raw material components. In one embodiment, silicon accounts for 2.5% by weight of the raw material components.

[0014] In the embodiments of the present application, Mg is a major alloying element, which mainly plays a strengthening role in forming the MgSi phase, but the electrical conductivity of the aluminum alloy is relatively sensitive to the Mg element, so the Mg content should not be too high. In addition, too high a Mg content will deteriorate the heat treatment properties of the aluminum alloy, causing the strength of the aluminum alloy to decrease after heat treatment.

[0015] Consider the amount of Mg5Si6 phase and Mg2Si phase generated and the strength and electrical conductivity of the aluminum alloy ingot. In one embodiment, the mass percentage of magnesium in the raw material component is within [0.2%, 1.0%]. In one embodiment, the mass percentage of magnesium in the raw material component is within [0.2%, 0.8%]. In one embodiment, the mass percentage of magnesium in the raw material component is within [0.2%, 0.6%]. In one embodiment, the mass percentage of magnesium in the raw material component is within [0.2%, 0.4%]. In one embodiment, the mass percentage of magnesium in the raw material component is within [0.4%, 1.0%]. In one embodiment, the mass percentage of magnesium in the raw material component is within [0.4%, 0.8%]. In one embodiment, the mass percentage of magnesium in the raw material component is within [0.5%, 0.8%]. In one embodiment, the mass percentage of magnesium in the raw material component is within [0.6%, 0.8%]. In one embodiment, magnesium accounts for 0.4% by weight of the raw material component. In one embodiment, magnesium accounts for 0.6% by weight of the raw material component. In one embodiment, magnesium accounts for 0.8% by weight of the raw material component.

[0016] In the embodiments of the present application, nickel (Ni) and cerium (Ce) are used as alloying elements, which mainly play the role of modifying and improving the performance of aluminum alloys. Ni promotes the nucleation of spherical α-Fe phase, increases the density of aluminum alloys, improves the fluidity and formability of aluminum alloys, and further improves the mechanical properties of aluminum alloys. Ce can purify aluminum liquid, spheroidize Fe-containing phases, and thus improve fluidity and plasticity, which is conducive to improving electrical conductivity.

[0017] During the casting process, trace amounts of Ni can increase the nucleation rate of the Fe-rich phase in the Al-Mg-Si alloy, thereby increasing the density of the spherical alpha iron-containing phase (α-Fe phase) and improving the fluidity and formability of the aluminum alloy. On the other hand, Ni addition can effectively improve the distribution, shape, and size of the Fe-containing phase, which is beneficial to the mechanical properties of the aluminum alloy, and improves its hot workability and resistance to bending. However, when the Ni content is too high, a coarse Al3Ni phase will be formed, which is not conducive to mechanical properties and electrical conductivity.

[0018] Trace amounts of Ce and Ni can spheroidize the Fe-containing phase, transforming it from a dendritic (β-AlFeSi phase) to a spherical (α-AlFeSi phase), thereby improving the fluidity and mechanical properties of the aluminum alloy. At the same time, the Ce element has high chemical activity and can be used as an aluminum liquid purifier to reduce the oxygen content in the aluminum liquid and improve the quality of the aluminum liquid. Ce can also react with Fe in the aluminum liquid to form AlFeCe phase, reduce the content of solid-solution Fe, and play a role in improving electrical conductivity. However, when the Ce content is too high, a block of Al 11The Ce3 phase will lead to a decrease in the mechanical properties and electrical conductivity of the alloy.

[0019] Considering the amount of spherical α-Fe phase and Al3Ni phase generated, as well as the strength properties, casting properties and electrical conductivity of the aluminum alloy ingot, in one embodiment, the mass percentage of nickel in the raw material components is within [0.01%, 2.30%]. In one embodiment, the mass percentage of nickel in the raw material components is within [0.01%, 2.00%]. In one embodiment, the mass percentage of nickel in the raw material components is within [0.01%, 1.70%]. In one embodiment, the mass percentage of nickel in the raw material components is within [0.01%, 1.50%]. In one embodiment, the mass percentage of nickel in the raw material components is within [0.01%, 1.00%]. In one embodiment, the mass percentage of nickel in the raw material components is within [0.01%, 0.80%]. In one embodiment, the mass percentage of nickel in the raw material components is within [0.01%, 0.50%]. In one embodiment, the mass percentage of nickel in the raw material components is within [0, 0.20%]. In one embodiment, the mass percentage of nickel in the raw material components is within [0.21%, 0.10%]. In one embodiment, the mass percentage of nickel in the raw material components is within [0.4%, 0.10%]. In one embodiment, the mass percentage of nickel in the raw material components is within [0.6%, 0.10%]. In one embodiment, the mass percentage of nickel in the raw material components is within [1.01%, 2.50%]. In one embodiment, the mass percentage of nickel in the raw material components is within [1.2%, 2.5%]. In one embodiment, the mass percentage of nickel in the raw material components is within [1.6%, 2.5%]. In one embodiment, the mass percentage of nickel in the raw material components is 0.2%. In one embodiment, the mass percentage of nickel in the raw material components is 0.5%. In one embodiment, the mass percentage of nickel in the raw material components is 1.0%.

[0020] Considering α-AlFeSi phase, AlFeCe phase and Al 11The amount of Ce3 phase generated and the casting performance and electrical conductivity of aluminum alloy ingots, in one embodiment, the mass percentage of cerium in the raw material components is within [0.01%, 0.4%]. In one embodiment, the mass percentage of cerium in the raw material components is within [0.01%, 0.3%]. In one embodiment, the mass percentage of cerium in the raw material components is within [0.01%, 0.25%]. In one embodiment, the mass percentage of cerium in the raw material components is within [0.01%, 0.15%]. In one embodiment, the mass percentage of cerium in the raw material components is within [0.01%, 0.10%]. In one embodiment, the mass percentage of cerium in the raw material components is within [0.01%, 0.05%]. In one embodiment, the mass percentage of cerium in the raw material components is within [0.01%, 0.02%]. In one embodiment, the mass percentage of cerium in the raw material components is within [0.11%, 0.50%]. In one embodiment, the mass percentage of cerium in the raw material components is within [0.2%, 0.5%]. In one embodiment, the mass percentage of cerium in the raw material components is within [0.3%, 0.5%]. In one embodiment, the mass percentage of cerium in the raw material components is within [0.4%, 0.5%]. In one embodiment, the mass percentage of cerium in the raw material components is 0.1%. In one embodiment, the mass percentage of cerium in the raw material components is 0.05%. In one embodiment, the mass percentage of cerium in the raw material components is 0.02%. In one embodiment, the mass percentage of cerium in the raw material components is 0.4%.

[0021] In an embodiment of the present application, the iron element is used to form a spherical α-Fe phase to increase the density of the aluminum alloy, improve the fluidity and formability of the aluminum alloy, and further improve the mechanical properties of the aluminum alloy. In one embodiment, the mass percentage of iron in the raw material components is within (0, 0.15%). In one embodiment, the mass percentage of iron in the raw material components is within (0, 0.1%). In one embodiment, the mass percentage of iron in the raw material components is 0.1%. In one embodiment, the mass percentage of iron in the raw material components is 0.05%.

[0022] In one embodiment, the trace iron element in the embodiment of the present application is derived from the aluminum raw material of the aluminum alloy, rather than being added additionally. In one embodiment, in order to improve the strength and electrical conductivity of the aluminum alloy ingot, additional iron may be added so that the mass percentage of iron in the raw material components is within (0, 0.15%).

[0023] It is particularly noteworthy that in the embodiments of the present application, the five main alloying elements of silicon, magnesium, nickel, cerium and iron do not exist in isolation, but are interrelated. In the embodiments of the present application, Al-Si-Mg has low density and high strength. During the casting process, the addition of Ni can increase the nucleation rate of the Fe-rich phase in the Al-Mg-Si alloy, thereby increasing the density of the spherical alpha iron-containing phase (α-Fe phase) and improving the fluidity and formability of the aluminum alloy. On the other hand, the addition of Ni can effectively improve the distribution, shape and size of the Fe-containing phase, which is beneficial to enhancing the mechanical properties of the aluminum alloy, improving its hot workability and resistance to bending. A trace amount of Ce addition can spheroidize the Fe-containing phase similar to Ni, so that it is transformed from a dendritic (β-AlFeSi phase) into a ball (α-AlFeSi phase), thereby improving the fluidity and mechanical properties of the aluminum alloy. At the same time, the Ce element has a high chemical activity and can be used as an aluminum liquid purifier to reduce the oxygen content in the aluminum liquid and improve the quality of the aluminum liquid. Ce can also react with Fe in aluminum liquid to form AlFeCe phase, reduce the content of solid solution Fe, and improve the conductivity. However, when the Ce content is too high, it will form a block of Al 11 Ce3 phase leads to the decrease of mechanical properties and electrical conductivity of aluminum alloy. Therefore, in the embodiment of the present application, the sum of the mass percentages of silicon, magnesium, nickel and cerium in the raw material components is less than or equal to 5%, so that the five elements can be coordinated with each other.

[0024] In one embodiment, the sum of the mass percentages of silicon, magnesium, nickel, cerium and iron in the raw material components is 4.5%. In one embodiment, the sum of the mass percentages of silicon, magnesium, nickel, cerium and iron in the raw material components is 4.0%. In one embodiment, the sum of the mass percentages of silicon, magnesium, nickel, cerium and iron in the raw material components is 3.5%. In one embodiment, the sum of the mass percentages of silicon, magnesium, nickel, cerium and iron in the raw material components is 3.0%. In one embodiment, the sum of the mass percentages of silicon, magnesium, nickel, cerium and iron in the raw material components is 2.5%. In one embodiment, the sum of the mass percentages of silicon, magnesium, nickel, cerium and iron in the raw material components is 2.0%.

[0025] In one embodiment, the phases inside the organizational structure of the aluminum alloy ingot include Al-Si-Mg-Ni-Ce phase or Al-Si-Mg-Ce phase. In one embodiment, the phases inside the organizational structure of the aluminum alloy ingot also include Mg2Si phase and Mg5Si6 phase to enhance the strength and electrical conductivity of the aluminum alloy profile. In one embodiment, the phases inside the organizational structure of the aluminum alloy ingot also include α-AlFeSi phase and AlFeCe phase to improve the fluidity, mechanical properties and electrical conductivity of the aluminum alloy. In one embodiment, the phases inside the organizational structure of the aluminum alloy ingot also include Al 11 Ce3 phase, in the embodiment of the present application, by controlling the Ce content, Al 11Ce3 phase is less controlled to avoid excessive Al 11 The Ce3 phase leads to a decrease in the mechanical properties and electrical conductivity of aluminum alloys.

[0026] In a second aspect, the present application provides a motor rotor of an asynchronous motor, the motor rotor comprising a rotor core and a rotor cage, the rotor cage being formed in the rotor core by integral die-casting of an aluminum alloy ingot as in the first aspect.

[0027] The motor rotor in the embodiment of the present application adopts a rotor cage formed by die-casting of an aluminum alloy ingot, which has resistance to thermal cracking, excellent room temperature yield strength and high temperature heat-resistant yield strength and excellent electrical conductivity.

[0028] In a third aspect, the present application provides an asynchronous motor, which includes a motor housing, a motor stator, a motor shaft and a motor rotor as in the second aspect, wherein the motor housing is used to sleeve and fix the motor stator, the motor stator is used to sleeve on the motor rotor, and the motor rotor is used to sleeve and fix on the motor shaft.

[0029] In the embodiment of the present application, the rotor cage of the motor rotor is formed by die-casting using an aluminum alloy ingot with the above-mentioned ratio, so that the motor rotor has resistance to thermal cracking, and at the same time has excellent room temperature yield strength and high temperature heat-resistant yield strength and excellent electrical conductivity, thereby obtaining an asynchronous motor that can meet the strength requirements and deformation requirements of the highest speed and overspeed.

[0030] In a fourth aspect, the present application provides a powertrain, which includes a reducer and an asynchronous motor as in the third aspect, wherein the motor shaft of the asynchronous motor is used for transmission connection with the input shaft of the reducer, and the output shaft of the reducer is used for transmission connection with the wheels of the electric vehicle.

[0031] The motor rotor of the asynchronous motor in the embodiment of the present application adopts the aluminum alloy ingot with the above-mentioned ratio, so that the motor rotor has resistance to thermal cracking, excellent room temperature yield strength and high temperature heat-resistant yield strength and excellent electrical conductivity, which meets the maximum speed and overspeed strength and deformation requirements of the asynchronous motor, thereby improving the reliability of the powertrain.

[0032] In a fifth aspect, the present application provides an electric vehicle, the electric vehicle comprising a frame, wheels and a powertrain as in the fourth aspect, the frame being used to fix the powertrain, and the powertrain being used to drive the wheels.

[0033] The powertrain in the embodiment of the present application includes an asynchronous motor. The motor rotor of the asynchronous motor adopts the aluminum alloy ingot with the above-mentioned ratio, so that the motor rotor has resistance to thermal cracking, excellent room temperature yield strength and high temperature heat-resistant yield strength and excellent electrical conductivity, which meets the maximum speed and overspeed strength and deformation requirements of the asynchronous motor, thereby improving the reliability of the powertrain and optimizing the overall performance of the vehicle. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments of the present application will be described below.

[0035] Figure 1 is a schematic diagram of the structure of an electric vehicle provided in an embodiment of the present application;

[0036] Figure 2 is a schematic diagram of the structure of a powertrain provided in an embodiment of the present application;

[0037] Figure 3a is a schematic diagram of the structure of the motor rotor provided in an embodiment of the present application;

[0038] Figure 3b is a schematic structural diagram of a rotor core provided in an embodiment of the present application;

[0039] Figure 3c is a schematic diagram of the structure of a rotor cage provided in an embodiment of the present application;

[0040] Figure 4 It is a schematic flow chart of a method for preparing an aluminum alloy ingot provided in an embodiment of the present application;

[0041] Figure 5 is a backscattered electron (BSE) image of an aluminum alloy provided in an embodiment of the present application;

[0042] Figure 6 This is the stress-strain curve of the aluminum alloy at 150°C provided in the examples of the present application. DETAILED DESCRIPTION

[0043] The technical solutions in the embodiments of the present application will be described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments.

[0044] For ease of understanding, the relevant technical terms involved in the embodiments of the present application are explained and described below.

[0045] Yield strength: It is the yield limit of metal materials when they yield, that is, the stress that resists slight plastic deformation. For metal materials without obvious yield phenomenon, the stress value that produces 0.2% residual deformation is specified as its yield limit, which is called conditional yield limit or yield strength.

[0046] Tensile strength: It is the critical value of the transition of metal from uniform plastic deformation to local concentrated plastic deformation, and it is also the maximum load-bearing capacity of metal under static tensile conditions. Tensile strength is the resistance to the maximum uniform plastic deformation of the material. Before the tensile specimen is subjected to the maximum tensile stress, the deformation is uniform, but after exceeding it, the metal begins to shrink, that is, concentrated deformation occurs.

[0047] Elongation: refers to an indicator that describes the plastic properties of a material. It is the percentage of the total deformation ΔL of the gauge section after the specimen is tensile fractured to the original gauge length L.

[0048] Electrical conductivity: Often referred to as conductivity, it is a measurement of a material's ability to carry an electric current. When a voltage is applied to a conductor, its charge carriers will flow in a certain direction, thus generating an electric current.

[0049] Nucleation: When the liquid phase is supercooled to the actual crystallization temperature, after a period of incubation, many orderly arranged small atomic groups begin to appear inside the liquid phase, which are called crystal embryos. When the crystal embryo reaches a certain critical size, it becomes a crystal nucleus that can exist stably and grow spontaneously. This process is called nucleation.

[0050] Nucleation rate: Nucleation rate refers to the number of crystal nuclei that form a new phase per unit volume per unit time. According to the classical nucleation and growth theory, phase transition is carried out through the formation of a crystal nucleus with a critical size and the further growth of the nucleus; the size of the nucleation rate will affect the speed of the phase transition process.

[0051] In the present application, a value within [a, b] indicates that the value includes a lower limit a, an upper limit b, and any value between a and b. [a, b] means that it is greater than or equal to a, and less than or equal to b. For example, a value within [0.5%, 1.5%] indicates that the value includes 0.5% and 1.5% and any value between 0.5% and 1.5%. In the present application, a value within (a, b] indicates that the value does not include a lower limit a, includes an upper limit b, and any value between a and b. (a, b] means that it is greater than a, and less than or equal to b. For example, a value within (0, 0.2%] indicates that the value includes 0.2% and any value between 0 and 0.2%.

[0052] The conductivity percentage is expressed as %IACS, which refers to the ratio of the resistivity specified in the international annealed copper standard to the resistivity of the sample in the same unit.

[0053] The present application provides an aluminum alloy ingot having good casting fluidity and resistance to thermal cracking tendency, as well as excellent room temperature yield strength and high temperature heat-resistant yield strength and excellent electrical conductivity, so that the motor rotor prepared from the aluminum alloy ingot can meet the strength requirements and deformation requirements of the highest speed and overspeed.

[0054] In one embodiment, an aluminum alloy ingot is provided, wherein the raw material components of the aluminum alloy ingot consist of aluminum, silicon, magnesium, nickel, cerium, iron and impurities, wherein:

[0055] The mass percentage of silicon in the raw material components is within [0.5%, 2.5%];

[0056] The mass percentage of magnesium in the raw material components is within [0.2%, 1.0%];

[0057] The mass percentage of nickel in the raw material components is within [0, 2.5%];

[0058] The mass percentage of cerium in the raw material components is within [0.01%, 0.5%];

[0059] The mass percentage of iron in the raw material components is within (0, 0.2%];

[0060] The sum of the mass percentages of silicon, magnesium, nickel, cerium and iron in the raw material components is less than or equal to 5%, and the remaining components are aluminum and impurities, and the impurity content is less than or equal to 0.3%.

[0061] In the embodiments of the present application, in the Al-Si-Mg alloy, magnesium (Mg) and silicon (Si) are the main strengthening elements, which mainly form a series of MgSi strengthening phases, such as Mg2Si, Mg5Si6, etc., after casting or heat treatment, to improve the mechanical properties of the aluminum alloy. Magnesium (Mg) and silicon (Si) can also form nano-scale β"-Mg5Si6 phase and β-Mg2Si phase during high-temperature smelting and casting, which serve as strengthening phases to improve the mechanical properties of the aluminum alloy.

[0062] In the embodiment of the present application, in the Al-Mg-Si alloy, a small amount of Si can effectively promote the nucleation of the strengthening phase MgSi phase, thereby improving the mechanical properties and effectively reducing the thermal cracking tendency of the alloy. However, when the Si content is too high, the alloy can form massive eutectic silicon at the grain boundary, which is not conducive to the mechanical properties and electrical conductivity of the alloy, and also increases the tendency of the alloy to intergranular corrosion.

[0063] Consider the amount of Mg5Si6 phase and Mg2Si phase generated and the strength and electrical conductivity of the aluminum alloy ingot. In one embodiment, the mass percentage of silicon in the raw material component is within [0.5%, 2.3%]. In one embodiment, the mass percentage of silicon in the raw material component is within [0.5%, 2.0%]. In one embodiment, the mass percentage of silicon in the raw material component is within [0.5%, 1.5%]. In one embodiment, the mass percentage of silicon in the raw material component is within [0.5%, 1.0%]. In one embodiment, the mass percentage of silicon in the raw material component is within [0.5, 1.2%]. In one embodiment, the mass percentage of silicon in the raw material component is within [1.5%, 2.5%]. In one embodiment, the mass percentage of silicon in the raw material component is within [2.0%, 2.5%]. In one embodiment, the mass percentage of silicon in the raw material component is 0.5%. In one embodiment, the mass percentage of silicon in the raw material component is 1.0%. In one embodiment, silicon accounts for 1.5% by weight of the raw material components. In one embodiment, silicon accounts for 2.0% by weight of the raw material components. In one embodiment, silicon accounts for 2.5% by weight of the raw material components.

[0064] In the embodiments of the present application, Mg is a major alloying element, which mainly plays a strengthening role in forming the MgSi phase, but the electrical conductivity of the aluminum alloy is relatively sensitive to the Mg element, so the Mg content should not be too high. In addition, too high a Mg content will deteriorate the heat treatment properties of the aluminum alloy, causing the strength of the aluminum alloy to decrease after heat treatment.

[0065] Consider the amount of Mg5Si6 phase and Mg2Si phase generated and the strength and electrical conductivity of the aluminum alloy ingot. In one embodiment, the mass percentage of magnesium in the raw material component is within [0.2%, 1.0%]. In one embodiment, the mass percentage of magnesium in the raw material component is within [0.2%, 0.8%]. In one embodiment, the mass percentage of magnesium in the raw material component is within [0.2%, 0.6%]. In one embodiment, the mass percentage of magnesium in the raw material component is within [0.2%, 0.4%]. In one embodiment, the mass percentage of magnesium in the raw material component is within [0.4%, 1.0%]. In one embodiment, the mass percentage of magnesium in the raw material component is within [0.4%, 0.8%]. In one embodiment, the mass percentage of magnesium in the raw material component is within [0.5%, 0.8%]. In one embodiment, the mass percentage of magnesium in the raw material component is within [0.6%, 0.8%]. In one embodiment, magnesium accounts for 0.4% by weight of the raw material component. In one embodiment, magnesium accounts for 0.6% by weight of the raw material component. In one embodiment, magnesium accounts for 0.8% by weight of the raw material component.

[0066] In the embodiments of the present application, nickel (Ni) and cerium (Ce) are used as alloying elements, which mainly play the role of modifying and improving the performance of aluminum alloys. Ni promotes the nucleation of spherical α-Fe phase, increases the density of aluminum alloys, improves the fluidity and formability of aluminum alloys, and further improves the mechanical properties of aluminum alloys. Ce can purify aluminum liquid, spheroidize Fe-containing phases, and thus improve fluidity and plasticity, which is conducive to improving electrical conductivity.

[0067] During the casting process, trace amounts of Ni can increase the nucleation rate of the Fe-rich phase in the Al-Mg-Si alloy, thereby increasing the density of the spherical alpha iron-containing phase (α-Fe phase) and improving the fluidity and formability of the aluminum alloy. On the other hand, Ni addition can effectively improve the distribution, shape, and size of the Fe-containing phase, which is beneficial to the mechanical properties of the aluminum alloy, and improves its hot workability and resistance to bending. However, when the Ni content is too high, a coarse Al3Ni phase will be formed, which is not conducive to mechanical properties and electrical conductivity.

[0068] Trace amounts of Ce and Ni can spheroidize the Fe-containing phase, transforming it from a dendritic (β-AlFeSi phase) to a spherical (α-AlFeSi phase), thereby improving the fluidity and mechanical properties of the aluminum alloy. At the same time, the Ce element has high chemical activity and can be used as an aluminum liquid purifier to reduce the oxygen content in the aluminum liquid and improve the quality of the aluminum liquid. Ce can also react with Fe in the aluminum liquid to form AlFeCe phase, reduce the content of solid-solution Fe, and play a role in improving electrical conductivity. However, when the Ce content is too high, a block of Al 11The Ce3 phase will lead to a decrease in the mechanical properties and electrical conductivity of the alloy.

[0069] Considering the amount of spherical α-Fe phase and Al3Ni phase generated, as well as the strength properties, casting properties and electrical conductivity of the aluminum alloy ingot, in one embodiment, the mass percentage of nickel in the raw material components is within [0.01%, 2.30%]. In one embodiment, the mass percentage of nickel in the raw material components is within [0.01%, 2.00%]. In one embodiment, the mass percentage of nickel in the raw material components is within [0.01%, 1.70%]. In one embodiment, the mass percentage of nickel in the raw material components is within [0.01%, 1.50%]. In one embodiment, the mass percentage of nickel in the raw material components is within [0.01%, 1.00%]. In one embodiment, the mass percentage of nickel in the raw material components is within [0.01%, 0.80%]. In one embodiment, the mass percentage of nickel in the raw material components is within [0.01%, 0.50%]. In one embodiment, the mass percentage of nickel in the raw material components is within [0, 0.20%]. In one embodiment, the mass percentage of nickel in the raw material components is within [0.21%, 0.10%]. In one embodiment, the mass percentage of nickel in the raw material components is within [0.4%, 0.10%]. In one embodiment, the mass percentage of nickel in the raw material components is within [0.6%, 0.10%]. In one embodiment, the mass percentage of nickel in the raw material components is within [1.01%, 2.50%]. In one embodiment, the mass percentage of nickel in the raw material components is within [1.2%, 2.5%]. In one embodiment, the mass percentage of nickel in the raw material components is within [1.6%, 2.5%]. In one embodiment, the mass percentage of nickel in the raw material components is 0.2%. In one embodiment, the mass percentage of nickel in the raw material components is 0.5%. In one embodiment, the mass percentage of nickel in the raw material components is 1.0%.

[0070] Considering α-AlFeSi phase, AlFeCe phase and Al 11The amount of Ce3 phase generated and the casting performance and electrical conductivity of aluminum alloy ingots, in one embodiment, the mass percentage of cerium in the raw material components is within [0.01%, 0.4%]. In one embodiment, the mass percentage of cerium in the raw material components is within [0.01%, 0.3%]. In one embodiment, the mass percentage of cerium in the raw material components is within [0.01%, 0.25%]. In one embodiment, the mass percentage of cerium in the raw material components is within [0.01%, 0.15%]. In one embodiment, the mass percentage of cerium in the raw material components is within [0.01%, 0.10%]. In one embodiment, the mass percentage of cerium in the raw material components is within [0.01%, 0.05%]. In one embodiment, the mass percentage of cerium in the raw material components is within [0.01%, 0.02%]. In one embodiment, the mass percentage of cerium in the raw material components is within [0.11%, 0.50%]. In one embodiment, the mass percentage of cerium in the raw material components is within [0.2%, 0.5%]. In one embodiment, the mass percentage of cerium in the raw material components is within [0.3%, 0.5%]. In one embodiment, the mass percentage of cerium in the raw material components is within [0.4%, 0.5%]. In one embodiment, the mass percentage of cerium in the raw material components is 0.1%. In one embodiment, the mass percentage of cerium in the raw material components is 0.05%. In one embodiment, the mass percentage of cerium in the raw material components is 0.02%. In one embodiment, the mass percentage of cerium in the raw material components is 0.4%.

[0071] In an embodiment of the present application, the iron element is used to form a spherical α-Fe phase to increase the density of the aluminum alloy, improve the fluidity and formability of the aluminum alloy, and further improve the mechanical properties of the aluminum alloy. In one embodiment, the mass percentage of iron in the raw material components is within (0, 0.15%). In one embodiment, the mass percentage of iron in the raw material components is within (0, 0.1%). In one embodiment, the mass percentage of iron in the raw material components is 0.1%. In one embodiment, the mass percentage of iron in the raw material components is 0.05%.

[0072] It is particularly noteworthy that in the embodiments of the present application, the five main alloying elements of silicon, magnesium, nickel, cerium and iron do not exist in isolation, but are interrelated. In the embodiments of the present application, Al-Si-Mg has low density and high strength. During the casting process, the addition of Ni can increase the nucleation rate of the Fe-rich phase in the Al-Mg-Si alloy, thereby increasing the density of the spherical alpha iron-containing phase (α-Fe phase) and improving the fluidity and formability of the aluminum alloy. On the other hand, the addition of Ni can effectively improve the distribution, shape and size of the Fe-containing phase, which is beneficial to enhancing the mechanical properties of the aluminum alloy, improving its hot workability and resistance to bending. A trace amount of Ce addition can spheroidize the Fe-containing phase similar to Ni, so that it is transformed from a dendritic (β-AlFeSi phase) into a ball (α-AlFeSi phase), thereby improving the fluidity and mechanical properties of the aluminum alloy. At the same time, the Ce element has a high chemical activity and can be used as an aluminum liquid purifier to reduce the oxygen content in the aluminum liquid and improve the quality of the aluminum liquid. Ce can also react with Fe in aluminum liquid to form AlFeCe phase, reduce the content of solid solution Fe, and improve the conductivity. However, when the Ce content is too high, it will form a block of Al 11 Ce3 phase leads to the decrease of mechanical properties and electrical conductivity of aluminum alloy. Therefore, in the embodiment of the present application, the sum of the mass percentages of silicon, magnesium, nickel and cerium in the raw material components is less than or equal to 5%, so that the five elements can be coordinated with each other.

[0073] In one embodiment, the sum of the mass percentages of silicon, magnesium, nickel, cerium and iron in the raw material components is 4.5%. In one embodiment, the sum of the mass percentages of silicon, magnesium, nickel, cerium and iron in the raw material components is 4.0%. In one embodiment, the sum of the mass percentages of silicon, magnesium, nickel, cerium and iron in the raw material components is 3.5%. In one embodiment, the sum of the mass percentages of silicon, magnesium, nickel, cerium and iron in the raw material components is 3.0%. In one embodiment, the sum of the mass percentages of silicon, magnesium, nickel, cerium and iron in the raw material components is 2.5%. In one embodiment, the sum of the mass percentages of silicon, magnesium, nickel, cerium and iron in the raw material components is 2.0%.

[0074] The components of the aluminum alloy ingot provided in the present application are determined by comprehensively considering the contribution of various chemical elements to the comprehensive performance indicators of the aluminum alloy (including yield strength, ductility, electrical conductivity, etc.). Through the combined action of the above-mentioned specific contents of each element, various properties are balanced, and an aluminum alloy ingot with excellent comprehensive properties such as a yield strength greater than 100 MPa and an electrical conductivity of 50% IACS is obtained.

[0075] In one embodiment, the phases inside the organizational structure of the aluminum alloy ingot include Al-Si-Mg-Ni-Ce phase or Al-Si-Mg-Ce phase. In one embodiment, the phases inside the organizational structure of the aluminum alloy ingot also include Mg2Si phase and Mg5Si6 phase to enhance the strength and electrical conductivity of the aluminum alloy profile. In one embodiment, the phases inside the organizational structure of the aluminum alloy ingot also include α-AlFeSi phase and AlFeCe phase to improve the fluidity, mechanical properties and electrical conductivity of the aluminum alloy. In one embodiment, the phases inside the organizational structure of the aluminum alloy ingot also include Al 11 Ce3 phase, in the embodiment of the present application, by controlling the Ce content, Al 11 Ce3 phase is less controlled to avoid excessive Al 11 The Ce3 phase leads to a decrease in the mechanical properties and electrical conductivity of aluminum alloys.

[0076] Figure 1 is a schematic diagram of the structure of an electric vehicle 1 provided in an embodiment of the present application, Figure 2 is a schematic diagram of the structure of a powertrain 10 provided in an embodiment of the present application, Figure 3a is a schematic diagram of the structure of the motor rotor 110 provided in an embodiment of the present application, Figure 3b is a schematic structural diagram of a rotor core 111 provided in an embodiment of the present application, Figure 3c 1 is a schematic diagram of the structure of the rotor cage 112 provided in an embodiment of the present application.

[0077] In one embodiment, if Figure 3a to Figure 3c As shown, a motor rotor 110 of an asynchronous motor 100 includes a rotor core 111 and a rotor cage 112. The rotor cage 112 is formed by integrally die-casting the aluminum alloy ingot provided in the present application in the rotor core 111. In one embodiment, the raw material composition of the rotor cage 112 is the same as the raw material composition of the aluminum alloy ingot provided in the present application.

[0078] In one embodiment, an asynchronous motor 100 includes a motor housing (not shown), a motor stator (not shown), a motor rotor 110 and a motor shaft 120, wherein the motor housing is used to sleeve and fix the motor stator, the motor stator is used to sleeve the motor rotor 110, the motor rotor 110 is used to sleeve and fix the motor shaft 120, and the motor stator can generate a magnetic field after current is passed through. The motor rotor 110 is sleeved and fixed to the motor shaft 120 and can rotate relative to the motor stator. There is an air gap between the motor rotor 110 and the motor stator. When the asynchronous motor 100 is working, the force of the motor stator on the motor rotor 110 enables the motor rotor 110 to rotate relative to the motor stator. When the motor rotor 110 rotates, it can drive the motor shaft 120 to rotate, and the asynchronous motor 100 outputs power through the motor shaft 120.

[0079] In one embodiment, if Figure 2 As shown, a power assembly 10 includes an asynchronous motor 100 and a reducer 200, wherein the asynchronous motor 100 includes a motor shaft 120, a motor stator and a motor rotor 110, and the reducer 200 includes a gear assembly, an input shaft and an output shaft, wherein the input shaft receives the power transmitted by the motor shaft 120 of the asynchronous motor 100 and transmits the power to the output shaft through the gear assembly. The gear assembly can be set as required, and can be a single-speed reduction gear assembly, a two-speed or multi-speed reduction gear assembly. The motor rotor 110 is fixedly sleeved on the motor shaft 120, and the motor stator drives the motor rotor 110 to rotate after receiving alternating current, thereby driving the motor shaft 120 to rotate. The motor shaft 120 of the asynchronous motor 100 is used for transmission connection with the input shaft of the reducer 200.

[0080] In one embodiment, if Figure 2 As shown, the powertrain 10 further includes a motor controller 300, which is fixed to the vehicle frame 20. The motor controller 300 is used to receive the direct current transmitted by the battery pack 30, and convert the direct current into alternating current and transmit it to the asynchronous motor 100. The asynchronous motor 100 is connected to the reducer 200 in a transmission manner. The asynchronous motor 100 is used to receive the alternating current and convert the electrical energy into mechanical energy, and transmit the mechanical energy to the reducer 200. The reducer 200 is connected to the wheel 40 in a transmission manner. The reducer 200 is used to transmit power to the wheel 40 to drive the wheel 40 to rotate.

[0081] In one embodiment, if Figure 1 As shown, an electric vehicle 1 includes a powertrain 10, a frame 20, a battery pack 30 and wheels 40. The frame 20 is used to fix the powertrain 10 and the battery pack 30. The battery pack 30 supplies power to the asynchronous motor 100 in the powertrain 10, and the asynchronous motor 100 drives the wheels 40 through the reducer 200. In the embodiment of the present application, the battery pack 30 can also be called a power battery. In the embodiment of the present application, the electric vehicle 1 refers to a wheeled device driven or towed by a power device.

[0082] Figure 4 It is a schematic flow chart of the method for preparing an aluminum alloy ingot provided in an embodiment of the present application.

[0083] In one embodiment, if Figure 4 As shown, the present application also provides a method for preparing an aluminum alloy ingot, comprising step S100, step S200 and step S300. The detailed steps are as follows.

[0084] Step S100, providing raw materials according to the component composition of the aluminum alloy ingot. The raw material components of the aluminum alloy ingot are composed of the following components in mass percentage: the mass percentage of silicon in the raw material components is within [0.5%, 2.5%]. The mass percentage of magnesium in the raw material components is within [0.2%, 1.0%]. The mass percentage of nickel in the raw material components is within [0, 2.5%]. The mass percentage of cerium in the raw material components is within [0.01%, 0.5%]. The mass percentage of iron in the raw material components is within (0, 0.2%]. The sum of the mass percentages of silicon, magnesium, nickel, cerium and iron in the raw material components is less than or equal to 5%, and the remaining components are aluminum and impurities, and the impurity content is less than or equal to 0.3%.

[0085] Pure aluminum is melted to obtain aluminum melt, and then the aluminum melt is subjected to slag removal.

[0086] Step S200, silicon, magnesium, nickel, cerium, and iron are added to the aluminum melt of step S100 in the form of single substance or master alloy to obtain aluminum alloy melt. In this step, the purpose is to solid-dissolve silicon, magnesium, nickel, cerium, and iron elements, convert each alloy element from large particles to small particles, and evenly disperse them in the aluminum melt. The aluminum alloy melt is cast and cooled to form an aluminum alloy ingot.

[0087] Step S300, remelting the aluminum alloy ingot obtained in step S200 and pouring it into a rotor aluminum casting mold for casting. After casting, a cast aluminum rotor is obtained and cooled to room temperature.

[0088] In the embodiments of the present application, the casting process may be gravity casting, high pressure die casting, low pressure casting or centrifugal casting.

[0089] The method for preparing the aluminum alloy ingot provided in the present application provides a method for preparing the aluminum alloy ingot, by setting specific elements and specific proportions, so that the prepared aluminum alloy ingot has high yield strength and electrical conductivity, and the aluminum alloy ingot has good thermal cracking resistance. The cast aluminum rotor obtained by remelting and casting the aluminum alloy ingot has high strength and high electrical conductivity, and is suitable for high speed operation.

[0090] In order to illustrate the beneficial effects of the raw material composition of the aluminum alloy ingot in the present application, the present application also makes examples 1-20 and comparative examples 1-10 and describes the test results, as shown in Table 1 and Table 2.

[0091] The method of preparing an aluminum alloy ingot and a cast aluminum rotor includes steps S100a, S200b and S300c. The detailed steps are as follows.

[0092] Step S100a, providing raw materials according to the specific composition of the aluminum alloy ingots of Examples 1-20 and Comparative Examples 1-10 in Table 1.

[0093] Step S200b, adding silicon, magnesium, nickel, cerium, and iron elements in the form of single substances or master alloys to the aluminum melt in step S100 to obtain different aluminum alloy melts.

[0094] Step S300c, remelting the aluminum alloy ingot obtained in step S200 and pouring it into a rotor aluminum casting mold for casting. After casting, a cast aluminum rotor is obtained and cooled to room temperature.

[0095] Table 1. Composition of aluminum alloy ingots in Examples 1-20 and Comparative Examples 1-10

[0096]

[0097] The aluminum alloy ingots prepared in the above Examples 1-20 and Comparative Examples 1-10 were subjected to the following performance tests:

[0098] The room temperature yield strength, high temperature yield strength and elongation of the material are tested using "GB / T228.1-2021 Tensile test of metal materials Part 1: Room temperature test method" and "GB / T228.2-2015 Tensile test of metal materials Part 2: High temperature test method".

[0099] The aluminum alloy ingots prepared with the above components are used to make mechanical properties test bars, and the shape and size of the test bars are in accordance with the provisions of "GB / T 16865-2023 Test specimens and methods for tensile testing of deformed aluminum, magnesium and their alloy products".

[0100] The tensile properties were tested using a CMT5205 electronic universal testing machine with a gauge length of 50 mm and a loading rate of 2 mm / min. The measured data were recorded. Six samples were tested at each formulation point, where the room temperature yield strength, high temperature yield strength and elongation were the average values ​​of the six data. The relative standard deviations of the room temperature yield strength and high temperature yield strength were the percentage ratios of the standard deviations of the six yield strength data to the average values. The test temperature for the room temperature yield strength was 22°C, and the test temperature for the high temperature yield strength was 150°C. The test results are entered in Table 2.

[0101] The conductivity of aluminum alloy is tested using the aluminum alloy conductivity eddy current test method specified in GB / T12966-2022.

[0102] Aluminum alloy conductivity test:

[0103] The conductivity meter used in the test is an eddy current conductivity meter with a frequency of 60kHz;

[0104] Test of the specimen: During the test, the probe of the conductivity meter is placed steadily on the center of the standard test block, and the conductivity meter is calibrated. The difference between the calibration value and the nominal value of the standard test block should not be greater than ±0.2Ms / m. Then, the probe of the conductivity meter is placed on the aluminum alloy cast cylindrical specimen prepared from the above composition, and the probe is in close contact with the test surface (the end face of the cylinder, the surface roughness Ra should be better than 1.6μm) for testing. The display screen of the eddy current conductivity meter can directly display the test value, and the conductivity value can be directly read in mega Siemens per meter (MS / m) or international annealed copper percentage (%IACS) as the display unit. The conductivity values ​​of at least 3 positions on the cylindrical specimen are tested respectively, and the average value is taken to obtain the true conductivity value. The test data obtained are shown in Table 2.

[0105] The determination standard of aluminum alloy die casting cracking is based on the standard specified in 3.5 of GB / T15114-2009. 3.5.2 stipulates that castings are not allowed to have cracks. Whether there are cracks in die casting cracking can be detected by naked eyes.

[0106] Table 2. Performance test results of aluminum alloy ingots of Examples 1-20 and Comparative Examples 1-10

[0107]

[0108] It can be seen from Table 2 that the yield strength of Examples 1 to 20 is greater than 100 MPa, the yield strength at room temperature can reach up to 140 MPa, the yield strength at high temperature can reach up to 131 MPa, the conductivity can reach up to 50% IACS, and the elongation can reach up to 16.5%.

[0109] Examples 1 to 4 in Table 2 are a single comparison of Si content in aluminum alloys. When the Si content is between [1, 2.5], within the scope of the present application, the increase in Si content in the aluminum alloy increases the amount of MgSi strengthening phase, strengthens the strengthening effect, gradually increases the room-temperature yield strength and high-temperature yield strength of the aluminum alloy, and gradually decreases the electrical conductivity.

[0110] Examples 5 to 11 and 19 are a single comparison of the Ni content in the aluminum alloy. When the Ni content is between [0, 2], within the scope of the present application, with the increase of the Ni content in the aluminum alloy, the room-temperature yield strength and high-temperature yield strength of the aluminum alloy gradually increase, and the electrical conductivity gradually decreases.

[0111] Examples 14 to 16 are a single comparison of Ce content in aluminum alloys. When the Ce content is between [0.05, 0.4], within the scope of the present application, the increase in Ce content in the aluminum alloy increases the room temperature yield strength, high temperature yield strength, and electrical conductivity of the aluminum alloy.

[0112] Example 17 and Example 18 are a single comparison of Mg content in aluminum alloys. The increase in Mg content increases the room-temperature yield strength and high-temperature yield strength of the aluminum alloy, while the electrical conductivity decreases from 48% IACS to 44% IACS.

[0113] Compared with Example 1, the Si content in Comparative Example 1 is reduced and is not within the scope of the present application, resulting in a reduction in the amount of MgSi strengthening phase, a poor strengthening effect, and poor fluidity, thereby causing the corresponding room-temperature yield strength and high-temperature yield strength in Table 2 to decrease, increase the thermal tendency, and make the castings prone to cracking.

[0114] Compared with Example 2, the Si content in Comparative Example 2 is increased, which is not within the scope of the present application, resulting in the formation of blocky eutectic silicon at the grain boundaries, and also increasing the tendency of grain boundary corrosion of the aluminum alloy, thereby causing the corresponding conductivity in Table 2 to decrease.

[0115] Compared with Example 1, the Mg content in Comparative Example 3 is reduced and is not within the scope of the present application, resulting in a reduction in the amount of MgSi strengthening phase and a poor strengthening effect, thereby causing the corresponding room-temperature yield strength and high-temperature yield strength in Table 2 to decrease.

[0116] Compared with Example 1, the Mg content in Comparative Example 4 is increased, which is not within the scope of the present application, resulting in an increase in the Mg in the solid solution state in the aluminum alloy, increasing the electron transfer resistance, and thus causing the corresponding conductivity in Table 2 to decrease.

[0117] Compared with Example 1, in Comparative Example 5, the Ni content is increased, which is not within the scope of the present application, so that the aluminum alloy forms a coarse Al3Ni phase, which increases the electron transfer resistance, thereby causing the corresponding conductivity in Table 2 to decrease.

[0118] Compared with Example 6, the Ce content in Comparative Example 6 is reduced and is not within the scope of the present application, which results in poor effects in purifying aluminum liquid and spheroidizing Fe-containing phases, thereby reducing the corresponding conductivity in Table 2.

[0119] Compared with Example 6, the Ce content in Comparative Example 7 is increased, which is not within the scope of the present application, so that the aluminum alloy will form a block of Al 11 The Ce3 phase is prone to cracking and increases the electron transmission resistance, which causes the corresponding strength and conductivity in Table 2 to decrease.

[0120] Compared with Example 1, Comparative Example 8 has a reduced Si content, an increased Ni content, and an increased Ce content, which are not within the scope of the present application, causing the aluminum alloy to have poor fluidity and form a coarse Al3Ni phase, thereby increasing the resistance to electron transport, thereby increasing the corresponding thermal tendency in Table 2, causing the casting to crack easily, and reducing the electrical conductivity.

[0121] Compared with Example 2, Example 19 does not add Ni element to the aluminum alloy, so that the nucleation of the spherical α-Fe phase cannot be promoted, thereby reducing the corresponding room temperature yield strength and high temperature yield strength in Table 2. However, compared with Comparative Examples 1 and 3, Example 19 has greater room temperature yield strength and high temperature yield strength, electrical conductivity of 50% IACS, and elongation of 16.5%.

[0122] Compared with Example 14, Example 20 does not add Ni element to the aluminum alloy, so that the nucleation of the spherical α-Fe phase cannot be promoted, thereby reducing the corresponding strength in Table 2. However, compared with Comparative Examples 1 and 3, Example 20 has greater room temperature yield strength and high temperature yield strength, electrical conductivity of 50% IACS, and elongation of 16.4%.

[0123] Compared with Example 19, the Si content in Comparative Example 9 is reduced and is not within the scope of the present application, resulting in a reduction in the amount of MgSi strengthening phase, a poor strengthening effect, and poor fluidity, thereby causing the corresponding strength in Table 2 to decrease, the thermal tendency to increase, and the casting to crack easily.

[0124] Compared with Example 20, the Ce content in Comparative Example 10 is increased, which is not within the scope of the present application, so that the aluminum alloy will form a block of Al 11 The Ce3 phase is prone to cracking and increases the electron transmission resistance, which causes the corresponding strength and conductivity in Table 2 to decrease.

[0125] Figure 5 This is a backscattered electron (BSE) image of the aluminum alloy provided in Example 1 of the present application.

[0126] like Figure 5 As shown, it is found through Example 1 that the aluminum alloy ingot die-casting flat plate sample provided in the present application has no cracks and has good thermal crack resistance.

[0127] Figure 6 This is the stress-strain curve of the aluminum alloy at 150° C. provided in Example 1 of the present application. The abscissa represents the stress-strain amplitude, and the ordinate represents the tensile strain intensity.

[0128] like Figure 6 As shown, in the process of increasing the tensile strain intensity from 0 to 140Mpa, the stress-strain amplitude only increases by 2.5%, and the stress-deformation amplitude is small, indicating that the aluminum alloy ingot in the present application has higher high-temperature yield strength and tensile strength, so that the motor rotor formed by die-casting of the aluminum alloy ingot in the present application can meet the maximum speed and overspeed strength requirements and deformation requirements of the motor rotor, thereby improving the motor performance.

[0129] The aluminum alloy ingots, the motor rotor of the asynchronous motor, the asynchronous motor, the powertrain and the electric vehicle provided in the embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and embodiments of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea; at the same time, for general technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific embodiments and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. An aluminum alloy ingot, characterized in that: The raw material components of the aluminum alloy ingot are composed of aluminum, silicon, magnesium, nickel, cerium, iron and impurities, among which: The mass percentage of silicon in the raw material components is within [0.5%, 2.5%]; The mass percentage of magnesium in the raw material components is within [0.2%, 1.0%]; The mass percentage of nickel in the raw material components is within [0, 2.5%]; The mass percentage of cerium in the raw material components is within [0.01%, 0.5%]; The mass percentage of the iron in the raw material components is within (0, 0.2%]; The sum of the mass percentages of the silicon, magnesium, nickel, cerium and iron in the raw material components is less than or equal to 5%, and the remaining components are the aluminum and impurities, and the impurity content is less than or equal to 0.3%.

2. The aluminum alloy ingot according to claim 1, characterized in that: The mass percentage of silicon in the raw material components is within [0.5%, 1.5%].

3. The aluminum alloy ingot according to claim 1, characterized in that: The mass percentage of silicon in the raw material components is within [1.5%, 2.5%].

4. The aluminum alloy ingot according to claim 1, characterized in that: The mass percentage of magnesium in the raw material components is within [0.2%, 0.4%].

5. The aluminum alloy ingot according to claim 1, characterized in that: The mass percentage of magnesium in the raw material components is within [0.4%, 1.0%].

6. The aluminum alloy ingot according to claim 1, characterized in that: The mass percentage of nickel in the raw material components is within [0, 0.20%].

7. The aluminum alloy ingot according to claim 1, characterized in that: The mass percentage of nickel in the raw material components is within [1.01%, 2.50%].

8. The aluminum alloy ingot according to claim 1, characterized in that: The mass percentage of cerium in the raw material components is within [0.01%, 0.10%].

9. The aluminum alloy ingot according to claim 1, characterized in that: The mass percentage of cerium in the raw material components is within [0.11%, 0.50%].

10. The aluminum alloy ingot according to claim 1, characterized in that: The sum of the mass percentages of the silicon, the magnesium, the nickel, the cerium and the iron in the raw material components is less than or equal to 4.0%.

11. The aluminum alloy ingot according to any one of claims 1 to 10, characterized in that: The phases inside the organizational structure of the aluminum alloy ingot include Al-Si-Mg-Ni-Ce phase or Al-Si-Mg-Ce phase.

12. A motor rotor of an asynchronous motor, characterized in that: The motor rotor comprises a rotor core and a rotor cage, and the rotor cage is formed in the rotor core by integrally die-casting using the aluminum alloy ingot as described in any one of claims 1 to 11.

13. An asynchronous motor, characterized in that: The asynchronous motor comprises a motor housing, a motor stator, a motor shaft and a motor rotor as claimed in claim 12, wherein the motor housing is used to sleeve and fix the motor stator, the motor stator is used to sleeve the motor rotor, and the motor rotor is used to sleeve and fix the motor shaft.

14. A powertrain, characterized in that: The power assembly includes a reducer and an asynchronous motor as claimed in claim 13, wherein the motor shaft of the asynchronous motor is used for driving connection with the input shaft of the reducer, and the output shaft of the reducer is used for driving connection with the wheels of the electric vehicle.

15. An electric vehicle, characterized in that: The electric vehicle comprises a frame, wheels and a powertrain as claimed in claim 14, wherein the frame is used to fix the powertrain, and the powertrain is used to drive the wheels.